PENGEMBANGAN LEMBAR KERJA SISWA BERORIENTASI MODEL PEMBELAJARAN GUIDED INQUIRY UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI SISTEM SIRKULASI KELAS XI SMA - Sherly Daberty Daberty; Darmawati '; Wan Syafi’i Syafi'i (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims to develop students worksheet oriented guided inquiry learning model to improve students critical thinking skills on the material circulation system in senior high school class XI. Research conducted at the Campus Biology Education and MAN 1 Pekanbaru from January to June 2015. The research used in this study refers to the development of R & D research approach using ADDIE model. Subjects were Basic Competency (KD) 3.6 biological material. The research begins with an analysis of the curriculum, syllabus and students worksheets compiled by MGMP. Then the students worksheet designed in accordance with the guided inquiry learning model and developed students worksheet with the model that aims to improve students critical thinking skills. Students worksheet draft I, which has been produced subsequently validated by 5 people validator, they are two education experts, two experts of the material and 1 teacher MA. Aspects assessed validation consisted of 3 aspects namely, the design aspect, pedagogical aspect and content aspect. After validated, than this students worksheet repaired appropriate the advice and input of the validator and the resulting draft worksheets II. Further trials conducted limited by spreading the questionnaire responses of the students MAN 1 Pekanbaru on 26 students of class XI IPA. Determination of class research determined randomly. Then do the revisions back to the students worksheet appropriate the advice and input of test results is limited resulting in critical thinking students worksheet final. The Reseacrh data result were analyzed by descriptive statistics. The results showed that the development of students worksheet oriented guided inquiry learning model to improve students critical thinking skills on the material at senior high school class XI in circulation system has been successfully developed by the category of very valid and very good. Student worksheet that has been developed has the potential to improve critical thinking skills. The mean results of the validation of 7 worksheets that have been developed successively ie 3:59, 3.63, 3.66, 3.66, 3.61, 3.73 and 3.78. Whereas the average of the results of limited testing of 7 worksheets that have been developed in succession, namely 3.72, 3.81, 3.74, 3.75, 3.73, 3.80 and 3.82. Keywords: development, student worksheets, guided inquiry, critical thinking, circulation system.